Collaboration as successful strategy against right-wing populism? The case of the centre-right coalition in Austria, 2000–2007. Issue 2 (23rd February 2016) - Fallend, Franz; Heinisch, Reinhard
Abstract : The article represents the first systematic study of the reactions of political parties and the media as well as national and transnational civil society actors to the rise and inclusion in government in 2000 of the Austrian right-wing populist Freedom Party (FPÖ). Specifically, it investigates the effectiveness of strategies aimed at ostracizing populist actors versus "defanging" them through incorporation in public office. The article finds that turning the FPÖ into a pariah has not been effective in moderating the party or curbing its success. Incorporation in public office has been more effective, however, leading to the near collapse of the FPÖ and the split of the party. Yet, the cause for such an outcome may be found less in the strategy itself by imposing some intrinsic mechanism of moderation but rather in the incompetence and inexperience of populist party politicians unfamiliar with public office. Exclusionary strategies have also the undesirable effect of playing into the narrative of populist actors of being persecuted by the political establishment thereby offering them another means of mobilization. The article concludes that the revival of the FPÖ shows that no strategy can yield lasting success unless the demand-side causes underlying radical right-wing populism are addressed.